Mycale (Oxymycale) klausjanusorum sp. nov. (Porifera: Demospongiae: Poecilosclerida) from Flores Sea deep water, Indonesia. in Deep Sea and Cave Sponges, Klautau, M., Pérez, T., Cárdenas, P. & de Voogd, N. (eds) - Van Soest, R.W.M. (Zootaxa, 2018)
A new species of the large genus Mycale Gray, 1867 is described, dredged from approximately 300 m depth in the Flores Sea region between the islands of Salayar and Bahuluang, Central Indonesia, during cruises of the Indonesian-Dutch Snellius II Expedition in 1984. Because its megascleres include oxeas the new species is classified as a member of the subgenus Oxymycale Hentschel, 1929, proposed to be named M. (O.) klausjanusorum sp. nov. to honour renowned colleagues Klaus Rützler and Jean (‘Janus’) Vacelet. It is characterized by an ectosomal skeleton consisting of bouquets of subtylostyle megascleres protruding beyond an ectosomal tangential confused layer of oxeas, which in turn rests on robust choanosomal bundles of mixed oxea and subtylostyle megascleres. The combination of two categories of megascleres, differentiated not only in size but also in morphology, the larger one of which is arranged in ectosomal bouquets, is a unique feature in the genus Mycale. A high diversity of the microscleres and large upper size of the anisochelae (up to 189 µm) are additional features of the new species. The subgenus Oxymycale is reviewed and its status as a monophyletic group of Mycale is discussed.